Synadenium umbellatum Pax. promotes cell cycle arrest and induces apoptosis in K-562 leukemia cells - Mariana Flavia da Mota; Polyana Lopes Benfica; Marize Campos Valadares (Universidade de São Paulo, 2012)
Chronic myeloid leukemia (CML) is a clonal myeloproliferative disease that shows apoptosis resistance. The introduction of imatinib mesylate has revolutionized the treatment of CML, but imatinib resistance may develop at any time and inevitably leads to disease progression. Synadenium umbellatum Pax. belongs to the Euphorbiaceae family and is popularly used in Brazil for the treatment of cancer. The cytotoxicity of Euphorbiaceae is associated with the ability of these plants and their bioactive compounds to induce apoptotic tumor cell death. Therefore, we aimed to investigate the cytotoxicity and the mechanisms of death induced by S. umbellatum extract in leukemic cells. S. umbellatum cytotoxicity was evaluated by trypan blue exclusion assay and flow cytometric analysis of the cell cycle; the mechanisms involved in K-562 cell death were investigated by light microscopy and flow cytometry. The results demonstrate that S. umbellatum is cytotoxic to leukemic cells in a concentration-dependent manner. Morphological analysis revealed that S. umbellatum treatment induced K-562 cell death by an apoptotic pathway. Furthermore, data indicate ROS overproduction, alterations in mitochondrial membrane potential, phosphatidylserine externalization and activation of caspase 9. Taken together, the results demonstrate that S. umbellatum extract arrested the cell cycle and triggered apoptosis at several levels in K-562 cells. A leucemia mielóide crônica (LMC) é uma doença mieloproliferativa clonal, que apresenta resistência à apoptose. A introdução do mesilato de imatinibe revolucionou o tratamento da LMC, porém a resistência ao imatinibe pode ser desenvolvida em qualquer tempo e, inevitavelmente, leva à progressão da doença. Synadenium umbellatum Pax. pertence à família Euphorbiaceae e é usado popularmente no Brasil para o tratamento do câncer. A citotoxicidade das Euphorbiaceae está associada com a capacidade dessas plantas e seus compostos bioativos em induzir apoptose em células tumorais. Portanto, este trabalho teve como objetivo investigar a citotoxicidade e os mecanismos de morte induzidos por S. umbellatum em células leucêmicas. A citotoxicidade de S. umbellatum foi avaliada pelo ensaio de exclusão do azul de tripano e a análise do ciclo celular foi feita por citometria de fluxo. Os mecanismos envolvidos na morte celular das células K-562 foram investigados por microscopia óptica e por citometria de fluxo. Os resultados demonstraram que S. umbellatum é citotóxico para células leucêmicas de uma maneira dependente da concentração. A análise morfológica revelou que o tratamento com S. umbellatum induziu as célula K-562 à morte por via apoptótica. Além disso, os dados indicam aumento de ERO S, alterações no potencial de membrana mitocondrial, externalização da fosfatidilserina e ativação de caspase 9. Em conjunto, os resultados demonstram que S. umbellatum promoveu retenção do ciclo celular das células K-562 e induziu estas células à morte por apoptose.